HUBUNGAN POLA MAKAN DENGAN RISIKO GASTRITIS PADA REMAJA - Fista Juliani; Herlina Herlina; Sofiana Nurchayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Adolescents tend to have a frequency of irregular eating, instant lifestyles and wrong eating patterns where adolescents like instant foods (fast food) that can cause gastritis. Symptoms in adolescents that often arise are pain and nausea. The aim of research is to know the relationship of eating pattern with the risk of gastritis in adolescents. The research design used is "Cross sectional" with the number of samples used as many as 81 people. The sampling technique used was proportionate stratified random sampling. Measurers used questionnaires about the frequency of eating, the type of eating, eating portion and the risk of gastritis that has been tested for validity and reliability. The analysis used is univariate analysis and bivariate analysis using Chi-Square test. Based on statistical test results obtained the frequency of eating with p value = 0,000 <0.05, the type of meal with p value = 0.000 <0.05, it can be concluded there is a relationship frequency and type of eating with the risk of gastritis. It is expected that students to keep the regularity of eating, the type of food consumed, and the portion of food eaten.  Keyword: Eating portion, frequency of eating, gastritis adolescent, type of eating